Biological and Chemical Co-surfactant for Fabrication of Antibacterial Silver Nanoparticles and Potential Application in Agriculture - Nguyen Nhat Nam (Tropical Life Sciences Research, 2025)
Silver nanoparticles (AgNPs) have been widely applied as antimicrobial materials. In this work, a new fabrication method of AgNPs has been proposed through a combination of tea seed saponin extraction as a non-ionic biological surfactant and cetyltrimethylammonium chloride (CTAC) as a co-surfactant. The morphology and optical properties of as-prepared AgNPs were analysed by SEM and UV-vis absorbance measurement, respectively. The results indicate that AgNPs obtained high homogeneous particle sizes with a mean diameter of 44.5 ± 3.8 nm. The optical property of AgNPs was exhibited through a UV-vis absorbance spectrum of 420 nm. In addition, the antibacterial behaviour of E. coli (ATCC 25922) was increased according to the AgNPs concentration. The diameter of inhibition zones was 12 mm, 14 mm and 16 mm under AgNPs concentrations of 0.8 ppm, 8 ppm and 80 ppm, respectively. Our initial trial treatment of AgNPs in young broccoli (Brassica oleracea) exhibited promising potential for plant protection in agricultural applications.